Estudo químico e avaliação das atividades antimicrobiana, antioxidante e antidiabética de espécies de Miconia (Melastomataceae) - Silva, Tiara da Costa (2023)
The genus Miconia (Melastomataceae) is distributed throughout the Brazilian biomes, with a large presence in the Cerrado. Some species are used in folk medicine and have been studied biologically and chemically. The aim of this work was to study the chemical composition and evaluate the antimicrobial, antidiabetic and antioxidant activities of nine species of Miconia (M. albicans, M. fallax, M. rubiginosa, M. chamissois, M. affinis, M. stenostachya, M. nervosa, M. elegans and M. cuspidata). The hexanolic (HE) and ethanolic (EE) extracts of the species, as well as the dichloromethane (DP), ethyl acetate (EAP) and n-butanol (BP) partitions of M. cuspidata, showed antibacterial activity against bacteria from the oral cavity, with a minimum inhibitory concentration (MIC) of 100 to 200 µg mL–1. The EE and partitions of M. cuspidata showed anti-Candida activity (MIC < 50 µg mL–1). The EE and partitions showed high antioxidant potential in the 2,2-diphenyl-1-picrylhydrazine (DPPH) radical scavenging, iron reduction capacity (FRAP) and oxygen radical scavenging (ORAC) methods. The EE inhibited α-amylase, with M. rubiginosa being the most active (IC50 = 0.74 ± 0.01 µg mL–1). The ability to inhibit glycoxidation was assessed using bovine serum albumin (BSA), fructose and methylglyoxal (MGO). The EE of Miconia species and the EAP, BP and AP of M. cuspidata, showed fructose-BSA glycoxidation inhibition values of over 80.00%. EE from M. rubiginosa (61.11 ± 0.47%) and PB (83.85 ± 1.30%) were the most active in inhibiting MGO-BSA glycoxidation. Through the analysis by high-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (HPLC-ES-EM/MS) of the EE of Miconia species, several classes of compounds were noted, including phenolic acids, flavonoids, fatty acid derivatives, triterpenoids, hydrolysable and condensed tannins. Fractionation of the HE of M. cuspidata led to the isolation of squalene (I) and β-sitosterol (II). Corosolic acid (III) and 3β-O-trans-p-coumaroyl corosolic acid (IV) were isolated from PD canferol-3-O-rutinoside was isolated from BP. Some Miconia species are being evaluated for the first time in relation to these biological activities and their chemical composition, thus contributing to the chemical-pharmacological knowledge of the Miconia genus.